Extreme-right violence in the Portuguese transition to democracy: Portugal’s Liberation Army (1974-1976) - Marchi, Riccardo (Fascism, 2022)
The Exército de Libertação de Portugal [ELP; Portugal’s Liberation Army] was one of the most infamous clandestine organizations active during the Portuguese transition to democracy, bringing together far-right militants from the deposed authoritarian regime. This organization has been considered the most dangerous terrorist group fighting for the restoration of Estado Novo’s regime. This article aims to challenge this statement, recurrently defended by international historiography, through an in-depth case study of the ELP, which is assessed in its genesis, structuring, ideological identity, strategy and operative capacity, permeability to repression, and dissolution. This study is based on a qualitative methodology triangulating data dispersed in the existing scientific and journalistic literature with data collected, unprecedently, in private archives and through face-to-face interviews with former ELP militants. Therefore, this paper is of importance to scholarship on the Portuguese transition to democracy, but also on the role of the extreme right in other post-authoritarian contexts, and on political violence in processes of democratization.